Globalization and the thought of unity in diversity of Badiuzzaman Said Nursi in the light of his magnum opus Risala-i Nur - Ajmal, Mohammad (Indonesian Journal of Islam and Muslim Societies, 2014)
Badiuzzaman Said Nursi had always looked at the world as one componentglorifying the one creator and testifying to His greatness. The universality hebelieved in, came into contradiction with the universality that results fromglobalization as it is generally understood and illustrated. People of economicallyless auspicious countries become themselves agents of globalization intheir own places. This is why the effects of globalization are more harmfulthan those of colonialism. Globalization recruits its soldiers from among peopleit invades and expands to swallow the remnants of their culture and selfesteemby making them follow the model of those who are more powerfuland who possess more.Badiuzzaman Said Nursi selalu memandang dunia sebagai salah satu komponenuntuk memuliakan Sang Pencipta dan menyaksikan kebesaran-Nya. Universalitasyang dipercayainya, berlawanan dengan universalitas yang dihasilkan dariglobalisasi seperti yang umum dipahami dan digambarkan. Masyarakat dariNegara-negara yang secara ekonomis kurang beruntung menjadikan diri mereka sendiri sebagai agen globalisasi di negara mereka sendiri. Inilah sebabnyamengapa efek globalisasi lebih berbahaya daripada kolonialisme. Globalisasimerekrut tentaranya dari kalangan orang-orang yang menjadi sasaran serangnyadan menelan sisa-sisa kebudayaan mereka serta harga diri dengan membuatmereka mengikuti model mereka yang lebih kuat dan memiliki kelebihan.